DAYA TARIK WISATA BUDAYA FESTIVAL CIAN CUI DI KOTA SELAT PANJANG PROVINSI RIAU - Nuansya, Ardi; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The cian cui culture festival is a water war festival held at the Lunar New Year celebration thatexisted 20 years ago, its philosophy can be interpreted as wet-basahan can be defined as a shareof sustenance because the water is the source of sustenance so by splashing equally by dividingkesesama. The purpose of this research is to find out (1) Variety of attraction in Cian CuiFestival in Meranti District (2) How to get the Cian Cui Festival (3) How to improve Cian CuiFestival as a tourist attraction. The design of this research is qualitative with deskruptiveapproach. The subjects of this study are key informants namely, Department of Tourism Youthand Sports District Merantidan Additional informants are community leaders Tiong Hoa-MelayuStrait Long and Society around Festiva budayal Cian Cui.Teknik data collection used isobservation, study documentation, and in-depth interview. Technical data analysis refers to theconcept of Milles and Huberman (1992). The results show that the cian cui cultural festival is nota religious event but it is a tradtion that is born from society to all people, and the variety of ciancui festival attraction is the uniqueness, beauty, and the values obtained in cian cui festival,because the festival This is all the tourists participate not participate as the audience only, and thepublic view of the cian cui festival is very good because many benefits are gained such astourism promotion event, trade at the time of the event took place and most important when twocultures melayu and china can unite and other . The government's planned improvement effortsto widen the streets around the festival are ongoing because of the targets reached by 15,000 to20,000 tourists, as well as improvements from other facilities and cultural festival cian cui eventitself.Keywords: attraction, festival, culture, Cian cui